Airway Morphology From High Resolution Computed Tomography in Healthy Subjects and Patients With Moderate Persistent Asthma. Issue 6 (8th April 2013) - Montesantos, Spyridon; Katz, Ira; Fleming, John; Majoral, Carolin; Pichelin, Marine; Dubau, Cecile; Piednoir, Benoit; Conway, Joy; Texereau, Joëlle; Caillibotte, Georges
ABSTRACT Models of the human respiratory tract developed in the past were based on measurements made on human tracheobronchial airways of healthy subjects. With the exception of a few morphometric characteristics such as the bronchial wall thickness (WT), very little has been published concerning the effects of disease on the tree structure and geometrical features. In this study, a commercial software package was used to segment the airway tree of seven healthy and six moderately persistent asthmatic patients from high resolution computed tomography images. The process was assessed with regards to the treatment of the images of the asthmatic group. The in vivo results for the bronchial length, diameter, WT, branching, and rotation angles are reported and compared per generation for different lobes. Furthermore, some popular mathematical relationships between these morphometric characteristics were examined in order to verify their validity for both groups. Our results suggest that, even though some relationships agree very well with previously published data, the compartmentalization of airways into lobes and the presence of disease may significantly affect the tree geometry, while the tree structure and airway connectivity is only slightly affected by the disease. Anat Rec, 296:852–866, 2013. © 2013 Wiley Periodicals, Inc.